2017
DOI: 10.1016/j.ijrobp.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of Radiomics and Metabolic Tumor Volumes in Radiation Treatment of Glioblastoma Multiforme

Abstract: Purpose To build a framework for investigation of the associations between imaging, clinical target volumes (CTVs), and metabolic tumor volumes (MTVs) features for better understanding of the underlying information in the CTVs and dependencies between these volumes. High-throughput extraction of imaging and metabolomic quantitative features from magnetic resonance imaging (MRI) and magnetic resonance spectroscopic imaging of glioblastoma multiforme (GBM) results in tens of variables per patient. In radiation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…CET 1 WI images are often used to determine the boundaries of gross tumors and to assess the extent of tumors as a means of assessing their invasiveness . T 2 WI sequences are sensitive to water tissue content and can be used to estimate cellular density and to detect the presence of edema . The ADC was used to describe diffusion processes that reflect various biomedical mechanisms and to estimate cellular density and the presence of edema .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CET 1 WI images are often used to determine the boundaries of gross tumors and to assess the extent of tumors as a means of assessing their invasiveness . T 2 WI sequences are sensitive to water tissue content and can be used to estimate cellular density and to detect the presence of edema . The ADC was used to describe diffusion processes that reflect various biomedical mechanisms and to estimate cellular density and the presence of edema .…”
Section: Discussionmentioning
confidence: 99%
“…37 T 2 WI sequences are sensitive to water tissue content and can be used to estimate cellular density and to detect the presence of edema. 38 The ADC was used to describe diffusion processes that reflect various biomedical mechanisms and to estimate cellular density and the presence of edema. 39 In our study, we illustrate that features extracted from the CET 1 WI sequence have a better performance than T 2 WI and ADC, which demonstrated that CET 1 WI is more useful than ADC maps in glioma grading.…”
Section: Discussionmentioning
confidence: 99%
“…The images from different sequences represent different tissue characteristics within the tumor. For example, enhanced T 1 WI could show the perfusion and extravasation characteristics of the contrast agent, while T 2 MRI sequences present edema as well as cell density, to a certain extent . T 1 WI spatial habitat diversity features have previously been demonstrated to be associated with clinical characteristics of epidermal growth factor receptor .…”
Section: Discussionmentioning
confidence: 99%
“…For example, enhanced T 1 WI could show the perfusion and extravasation characteristics of the contrast agent, while T 2 MRI sequences present edema as well as cell density, to a certain extent. 39 T 1 WI spatial habitat diversity features have previously been demonstrated to be associated with clinical characteristics of epidermal growth factor receptor. 40 This may also explain why more enhanced T 1 WI features were selected than the other two sequences in the combination radiomic features.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics features are a promising additional data type for oncologic outcome prediction and tumor control probability models (76). Multiple manuscripts have been published using radiomics to predict radiation response, in some cases with prediction power outperforming standard clinical variables (77)(78)(79)(80)(81)(82), though not in all (83). Radiomicsbased statistical approaches can predict various radiation normal tissue complication probabilities including radiation pneumonitis, xerostomia, and rectal wall toxicity (84)(85)(86)(87)(88)(89).…”
Section: Tumor Control Probability and Normal Tissue Complication Promentioning
confidence: 99%